Impact of Lupin and Grass Pea Mixture Meal as Dietary Inclusion on Body Composition and Haematological Parameters of Nile Tilapia Fingerlings in a Recirculation Aquaculture System - Tsegay Fisseha; Akewake Geremew; Tadesse Fetahi; Kasim Abass (Aquaculture, Fish and Fisheries, 2025)
ABSTRACT The study investigated the effects of fishmeal replacement with a mixture of lupin and grass pea meal (LGM) at inclusion levels of 0%, 25%, 50% and 75% as potential plant protein sources in the diets of Nile tilapia fingerlings on body composition and haematological parameters. Experimental diets were formulated to be iso‐nitrogenous (36 g 100 g−1), iso‐lipidic (10 g 100 g−1) and iso‐energetic (18 kJ g−1), fed at 6%–10% of their body weight per day. A total of 276 fingerlings with an average initial body weight of 1.37 ± 0.06 were stocked into four treatments, each in triplicate, using a completely randomized design for 12 weeks. Results showed no significant differences (p < 0.05) in Hct, RBCs, WBCs and MCV across all LGM diet levels. However, an increasing trend of Hb, MCH and MCHC has been shown by fishes fed with LGM75. MCH and MCHC values decreased in groups fed LGM25 and LGM50 compared to the control and LGM75. MCV did not show significant differences with higher LGM protein levels. The differential WBC count of Nile tilapia fingerlings was dominated by lymphocytes (% mm−3), and lymphocytes, monocytes, neutrophils and eosinophils were identified, but basophils were not counted. Monocyte and eosinophil counts were not significantly different (p < 0.05) from the control diet. Fish fed LGM75 and LGM50 had higher HSI than those on the control and LGM25, with an increasing trend observed at higher LGM protein levels. LGM proteins have positively influenced carcass composition, haematological parameters and growth, suggesting improved overall health, vitality and a cost‐effective fishmeal alternative. Furthermore, successful uses of LGM proteins lead to healthier fish populations, improved resilience against diseases, survival rates and a more sustainable aquaculture. These feed ingredients can support fish farmers and contribute to affordable and accessible feed alternatives supporting a sustainable aquaculture industry. Overall, there are promising nutritional and haematological justifications for replacing fish meal with LGM protein sources in Nile tilapia diets.